Evaluation of biochar from palm oil waste as a carbon sink and as sustainable cement replacement in building materials - Aman, Aan Mohammad Nusrat (2025)
Over the years, there has been a high demand of concrete in the construction industry due to its strength and durability. However, the production of cement, a key component of concrete, has caused high carbon dioxide emissions, negatively affecting the environment. To address this issue, recent research has explored sustainable supplementary cementitious material such as biochar, which offers increased strength and enhanced properties for concrete and mortar composites. This research focuses on the usability, efficiency, and sustainability of palm oil waste biochar as a cement replacement for carbon sequestration. The selected biochar palm kernel shell and empty fruit bunch were produced through pyrolysis. By recycling palm oil waste and converting it into biochar for construction, this approach promotes sustainable practices within the palm oil industry. This study investigates both the optimisation of biochar production through pyrolysis and its utilisation as a supplementary cementitious material. Response surface methodology was used to optimise pyrolysis parameters. The optimised pyrolysis parameters are 409°C, 15°C/min, 120 minutes for palm kernel shells and 455°C, 15°C/min, 20 minutes for empty fruit bunch. Cement replacement from 1 to 8% was casted with biochar mortar composites and mechanically tested through compressive strength, density, porosity, water absorption and flexural strength to understand the behaviour of biochar with cement. Mortar composites with 4% empty fruit bunch biochar pyrolysed at 455°C were found to be the optimum percentage with improved mechanical properties. Concrete composites with 4% biochar were compared and evaluated by the same mechanical tests. The concrete composites with 4% palm kernel shells pyrolysed at 409°C proved to be the optimum mix.